The impact of the national reimbursement drug list negotiation policy on the accessibility and utilization of evolocumab and alirocumab in different levels of hospitals: an interrupted time series analysis - Tang, Wan; Li, Wei; Zhang, Anqi; Wu, Huanhuan; Lu, Wei; Fan, Yan (Frontiers in Pharmacology, 2025)
ObjectiveIn December 2021, evolocumab and alirocumab were included in the National Reimbursement Drug List Negotiation (NRDLN), with implementation commencing in January 2022. This study aimed to evaluate the impact of the NRDLN policy on the clinical utilization of two novel lipid-lowering agents in different levels of hospitals.MethodsData on evolocumab and alirocumab were collected from 910 tertiary and secondary public general hospitals across 31 provinces or autonomous regions in China (from January 2020 to December 2023) via the China Pharmaceutical Information Network (CPIN). Interrupted Time Series (ITS) analysis was employed to evaluate changes in drug availability, Defined Daily Doses (DDDs), and Defined Daily Dose cost (DDDc) before and after the inclusion of these drugs in the NRDLN.ResultsThe inclusion of evolocumab and alirocumab in the NRDLN was followed by a substantial increase in their availability, with alirocumab (β3 = 0.207 vs. 0.701) showing a larger improvement in availability than evolocumab. Following policy implementation, DDDs of both drugs maintained a persistent upward trend, and those in tertiary hospitals (β3 = 71041.810 Vs. 43625.730) consistently showed higher values than secondary hospitals (β3 = 3753.400 Vs. 3034.650). However, the disparity in trend slopes between hospital tiers gradually narrowed over time. A distinct breakpoint and significant trend changes in DDDc were observed for evolocumab (β2 = −53.587) and alirocumab (β2 = −79.280) after policy implementation, with DDDc values markedly lower then.ConclusionThe inclusion of evolocumab and alirocumab in the NRDLN has significantly enhanced their accessibility and eased the medication burden on patients. Furthermore, the disparity in the adoption and utilization of PCSK9 inhibitors across hospital tiers has progressively narrowed, thereby safeguarding equitable health outcomes and advancing population health security.